Aboveground biomass and carbon stock assessment of forest plantations in Mindanao - Tandug, Leuvina M. (Sylvatrop, 2012)
The study was conducted to estimate biomass accumulation of five forest tree plantation species (bagras, falcata, mahogany, mangium and yemane) and quantify the carbon stock of the commercial plantations in Mindanao. The plantations surveyed had a wide range of stand ages (1-25 years old) and planting density of 191-10,000 trees/ha. Allometric equations developed by ERDB in 2009 based on diameter at breast height and total height were used to predict the tree aboveground biomass and total carbon stock of the plantations. Based on 273 plots established inside the plantations, the biomass density of the five species ranged from 1 to 1,109 tons ha-1 and carbon density ranged from 1 to 523 tons C ha-1 at different sites. The mean biomass of the five species is 183.1 tons ha-1 for an average stand of 12 years old. As a whole, the plantations (2,002 ha) contained a total aboveground biomass of 268,228 tons which has sequestered an equivalent of 126,181.9 tons CO2 from the atmosphere. Region 12, having the highest number of planted forests (1,146 ha), gave the highest total biomass of 111,108.6 tons. This was followed by Region 13 (71,174.4 tons) and Region 11 (34,546.9 tons), respectively. The total carbon stock of the plantations surveyed was 126,181.9 tons C which is equivalent to 463,084 tons CO2 sequestered from the atmosphere. Among the five forest tree species evaluated, mangium stored and sequestered the biggest amount of carbon. With a total of 328.3 ha of plantations, mangium was able to store 53,930 t C. This represents 42.8% of the total amount of carbon stored by the plantations in Mindanao.